A (Re)Produção do Espaço de Anápolis/GO: a trajetória de uma cidade média entre duas metrópoles, 1970-2000 - Luz, Janes Socorro da (2009)
The research examines the issue of territory and considers the importance of territorial division of labor in the configuration of intermediate cities. In this sense, is developed in order to understand the process of (re) production of Anápolis, the State of Goiás, while median-sized city, located in a strategic area between two cities, Brasília and Goiânia. Also, highlights the changes that influence the characterization of midtown and in the exercise of regional command, This organized into four basic parts: the first involves a discussion about space and territory with emphasis on the economic approach, citing the assumptions that guide the discussion on the city average and the research object on screen, the second highlights the process ownership and modernization of Goiás territory which affects the spatial organization and territorial division of labor, entered the city of Anápolis as in the regional center which is intended as a meeting point of investment and population. The third examines the evolution of the city and the different dimensions in which, Anápolis, projects its influence in a continuous and discontinuous, through the territorial reserves that characterize the subspaces contained in the territory where the city is central. The fourth part, in turn, characterizes the economic and political dimensions, highlighting the relevance of the same over the constitution of the city, too, believes that the city average is in constant transformation that promotes the re-fictionalization and develops new roles and activities. Finally, says the question of the relativity of the issue of location in the configuration of the city as mean when discussing the case of Anápolis and its position between Goiânia and Brasília.